The Mysuru stUdies of Determinants of Health in Rural Adults (MUDHRA), India - Padukudru Anand Mahesh; Komarla Sundararaja Lokesh; Purnima Madhivanan; Sindaghatta Krishnarao Chaya; Biligere Siddaiah Jayaraj; Koustav Ganguly; Murali Krishna (Epidemiology and Health, 2018)
Between 2006 and 2010, in 16 randomly selected villages in rural areas of Mysore district, in south India, 8,457 subjects aged 30 and above were screened for symptoms of chronic respiratory disease. Of the 8,457 subjects, 1,692 were randomly invited for further evaluation of lung function and chronic obstructive pulmonary disease (COPD) by spirometry, and 1,085 of these subjects underwent lung function assessments for prevalent COPD and its risk factors. These 1,085 subjects, who were then aged between 35 and 80 years, constituted the Mysuru stUdies of Determinants of Health in Rural Adults (MUDHRA) cohort. Among other findings, threshold of biomass fuel smoke exposure suitable for use as a dichotomous risk factor for the diagnosis of chronic bronchitis was established, with a minimum biomass smoke exposure index of 60 found to be significantly associated with an elevated risk of developing chronic bronchitis. Five years later (between 2014 and 2016), 869 of the 1,085 participants were followed up with repeat lung function assessments for incident COPD and all-cause mortality. A subset of these participants (n=200) underwent blood tests for vitamin D levels, antioxidant activity, an assessment for anxiety and depression, and another subset (n=98) underwent a bioplex assay for 40 serum cytokines.